Penerapan Strategi Pemasaran Digital untuk Pengenalan Produk di Kampung Batik Giriloyo Yogyakarta - Romadon, Taufik; Suryani Putri; Suci Handayani; Bakti Sentosa; M.Dedek Hamdalah Putra; Muhammad iqbal (Jurnal Pengabdian, 2025)
Batik Giriloyo is known for its high-quality traditional batik products, but it faces challenges in expanding its market reach and increasing brand awareness beyond the local area. This community service project aims to assist Batik Giriloyo in boosting sales and product recognition through the implementation of digital marketing strategies. The project focuses on training artisans to utilize digital platforms such as social media and e-commerce to enhance product visibility. Key activities included workshops on the effective use of social media and content creation, such as product photography and videos. The results of this initiative show that artisans have become more skilled in digital marketing, which has led to greater recognition of Batik Giriloyo products at both local and national levels. This emphasizes the importance of digital literacy for SMEs and demonstrates that effective digital marketing can be a powerful tool for growth. The project establishes a foundation for sustainable digital engagement and better business development.